Abdominal wall herniation in working Moroccan equids: 14 cases (2016–2017). (23rd March 2020) - Khairoun, A.; Kay, G.
Summary: Hernia of the abdominal musculature was seen in 14 working equids (1% of total admissions) during the 14‐month period between October 2016 and December 2017. Animals with hernias of less than 2 months' duration (six animals) were treated conservatively with compressive abdominal bandaging whereas those with hernias of more than 2 months' duration (five animals) were treated surgically with a primary closure of the defect. Surgical repair was not possible in three individuals due to the large size of the defect, location and lack of availability of prosthetic mesh. Of the 11 equidae treated, all showed complete resolution of the hernia by the time of discharge, and follow‐up with owners, between 5 and 16 months post‐treatment, revealed that no recurrence of the ruptures.